2012
DOI: 10.1002/acp.2881
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Handwriting Speed, Working Memory, Language Comprehension and Outlines to Lecture Note‐taking and Test‐taking among College Students

Abstract: SummaryA previous investigation of the cognitive processes underlying note‐taking found that handwriting speed was the only significant predictor of notes, and notes were the only significant predictor of test performance. This investigation sought to extend these results by evaluating the effects of handwriting speed, language comprehension, two measures of working memory (complex span and executive attention) and an outline on note‐taking and test performance (written summary). Participants were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 69 publications
3
52
2
2
Order By: Relevance
“…WMC, for example, sometimes predicts students' note quality (e.g., Bui, Myerson, & Hale, 2013;Hadwin, Kirby, & Woodhouse, 1999;Kiewra & Benton, 1988;McIntyre, 1992), but sometimes does not (e.g., Bui et al, 2013;Peverly et al, 2007Peverly et al, , 2013, perhaps because WMC effects depend on notetaking strategies (Bui & Myerson, 2014).…”
Section: Note-taking As An Intervention To Promote Focused Attention mentioning
confidence: 99%
“…WMC, for example, sometimes predicts students' note quality (e.g., Bui, Myerson, & Hale, 2013;Hadwin, Kirby, & Woodhouse, 1999;Kiewra & Benton, 1988;McIntyre, 1992), but sometimes does not (e.g., Bui et al, 2013;Peverly et al, 2007Peverly et al, , 2013, perhaps because WMC effects depend on notetaking strategies (Bui & Myerson, 2014).…”
Section: Note-taking As An Intervention To Promote Focused Attention mentioning
confidence: 99%
“…Not only the presence of an outline thus seems to be of importance (cf. Peverly et al, 2013), but also the format of the outline. Bui and McDaniel (2015) also found that the format of the outline matters.…”
Section: Structure Of Note-takingmentioning
confidence: 99%
“…A large number of studies has explored the effects of note quality on memory for lecture content (Aiken et al, 1975;Einstein, Morris, & Smith, 1985, study 2;Fisher & Harris, 1973;Kiewra & Benton, 1988;Kiewra, Benton, & Lewis, 1987;Peverly et al, 2007Peverly et al, , 2013Peverly & Sumowski, 2012). These studies have consistently shown that better note quality is related to better performance on memory tests administered afterwards.…”
Section: Note Contentmentioning
confidence: 99%
“…Handwriting is one of the five aspects; vocabulary, sentences, comprehension, and tenses are the others. Peverly et al (2013) have carried out their study to evaluate handwriting speed as one of a group of factors that have their effect on the performance of college students. The study has uncovered the importance of speedy handwriting for positive quality and quantity fulfillment of different kinds of writing among children and adults.…”
Section: Previous Literaturementioning
confidence: 99%
“…Peverly et al (2013) refer to the importance of speedy handwriting for taking notes which are considered an effective aid for the personal memory. Since the information is usually quickly forgotten, note-takers need to write it quickly before it is forgotten.…”
Section: Handwriting and The Students' Academic Performancementioning
confidence: 99%